(untitled) (Journal of Material Science and Technology Research, 2024)
Abstract: Natural fiber composites (NFC) are increasingly recognized for their sustainability and versatility. Abaca fiber is one of the prominent natural fibers that are sourced from the leaf sheaths of the abaca plant. This study provides an overview of the comparison of the mechanical properties and water uptake behavior of surface-modified N2 plasma and alkali treated abaca fiber-reinforced epoxy composites with granite powder used as fillers. It mentions the use of varying filler content (0 wt.%, 10 wt.%, 20 wt.%, and 30 wt.%) in both the pre-treated composites and compares their properties. Plasma-treated granite filler samples showed superior tensile strength and flexural properties, despite a negative effect on impact properties. A lower water absorption is observed in plasma-treated composites with fillers compared to those without fillers. Overall, the potential of surface modification techniques with granite-based mineral fillers is apparent in improving the performance of N2 plasma treated NFCs, thus expanding their applications across different industries aiming for the good mechanical hygroscopic properties.